A RARE CASE REPORT OF PARATESTICULAR RHABDOMYOSARCOMA IN AN ADULT PATIENT - Mussadique Ali (Army Medical College Rawalpindi, 2021)
Rhabdomyosarcoma is a malignancy of mesenchymal tissue origin typically occurring in childhood and adolescence, with an incidence rate of of 4.3 patients per million population per anum. Primary rhabdomyosarcoma of para-testicular origin is an infrequent condition, making up to 7% of all the cases of rhabdomyosarcoma tumors in children and adolescents. Here we describe a case of a 25 years old man with left paratesticular solid mass. He underwent left sided orchiectomy with histopathology revealing paratesticuler embryonal rhabdomyosarcoma. He underwent definitive chemo-radiotherapy and orchidopexy with complete remission and is on active surveillance for 4 years.